Systematic review of the beneficial effects of thrombin and vitamin K inhibitors on migraine treatment - Nogueira, Eduardo de Almeida Guimaraes; Couto, Angela dos Anjos; Grossi, Beatriz Moraes; Nunes, Gabriela Dias; Hanada, Taliê Zanchetta B.; Fragoso, Yara Dadalti (Headache Medicine, 2019)
Background: Prophylactic migraine therapy includes beta-blockers, anticonvulsants, tricyclic antidepressants and calcium channel modulators. These drugs have been serendipitously identified as agents capable of migraine control. In order to reduce drug intake, interactions and potential adverse events, patients who have high blood pressure and migraine are often prescribed beta-blockers or calcium channel antagonists. Patients with epilepsy and migraine can use anticonvulsants, those with depression and migraine can be treat with antidepressants, and those with heart arrhythmia or recurrent vertigo and concomitant migraine can benefit from use of calcium channel antagonists. The beneficial effects of vitamin K or thrombin inhibitors on migraine attacks were first described decades ago, and there may be a place for these drugs in migraine prophylaxis. Objective: To investigate the potential beneficial effects of this class of anticoagulants regarding prevention of migraine attacks. Method: Systematic review of the literature including papers with patients’ results. Results: A search of the literature yielded 16 papers with data on patients using inhibitors of vitamin K or thrombin for thromboembolic conditions. Articles typically reported on single cases or small case series. In all but one of these reports, the effect of the drug was remarkable in decreasing migraine severity. Conclusion: Although the level of recommendation is low due to the lack of proper clinical trials, vitamin K or thrombin inhibitors may be useful for migraine management in patients who also require anticoagulation. For these individuals, use of this class of anticoagulants could avoid adding extra drugs for migraine management.